2006
DOI: 10.1021/nl061018w
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Electronic Properties of Self-Organized Poly(3-dodecylthiophene) Monolayers by Two-Dimensional Scanning Tunneling Spectroscopy Imaging at the Single Chain Scale

Abstract: Regioregular poly(3-dodecylthiophene) films self-organized on highly oriented pyrolytic graphite have been investigated by scanning tunneling microscopy and two-dimensional scanning tunneling spectroscopy (STS). Simulated spectra in very good agreement with the experimental data have been obtained by a method combining ab initio and semiempirical approaches, which allows a careful discussion of the polymer electronic states. From the experimental data, with the support of modeling, it is shown that the STS spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 48 publications
1
46
0
Order By: Relevance
“…In the case of organic photovoltaics and light-emitting devices, optimizing the π-stacking of conjugated molecules is essential to tuning transport properties and exciton lifetimes 9,10 . Most studies in this field have focused on optimizing bulk device characteristics by altering molecular substituents 11 , post-growth annealing 12,13 or other processing steps 14 , or have used scanning tunnelling microscopy and spectroscopy to measure charge transport across multilayer stacks of conjugated molecules 15 . Combined optical absorption spectroscopy experiments and theoretical work on coupling in planar naphthalene dimers has also been published 16 .…”
mentioning
confidence: 99%
“…In the case of organic photovoltaics and light-emitting devices, optimizing the π-stacking of conjugated molecules is essential to tuning transport properties and exciton lifetimes 9,10 . Most studies in this field have focused on optimizing bulk device characteristics by altering molecular substituents 11 , post-growth annealing 12,13 or other processing steps 14 , or have used scanning tunnelling microscopy and spectroscopy to measure charge transport across multilayer stacks of conjugated molecules 15 . Combined optical absorption spectroscopy experiments and theoretical work on coupling in planar naphthalene dimers has also been published 16 .…”
mentioning
confidence: 99%
“…Collective Reactivity of Molecular Chains Self-Assembled on a Surface Peter Maksymovych, 1,2 Dan C. Sorescu, 3 Kenneth D. Jordan, 1 John T. Yates Jr. 1,4 * Self-assembly of molecules on surfaces is a route toward not only creating structures, but also engineering chemical reactivity afforded by the intermolecular interactions. Dimethyldisulfide (CH 3 SSCH 3 ) molecules self-assemble into linear chains on single-crystal gold surfaces.…”
mentioning
confidence: 99%
“…Note that the thickness of our films lies intermediate to values reported previously for PDDT on other substrates. Scifo et al used STM to measure the thickness in UHV of a PDDT film drop cast on highly oriented pyrolytic graphite (HOPG) and reported a film thickness of 0.24 ± 0.04 nm [19]. In contrast, Terada et al [20] reported poly(3-hexylthiophene) (P3HT) on H-terminated Si(100) in UHV to be 0.5 nm thick.…”
Section: Resultsmentioning
confidence: 99%